Framing Analysis of the 2024 Presidential Election Coverage on www.rri.co.id and www.antaranews.com - Vebiyanti, Vivi; Jasafat; Syahril Furqany (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This research analyzes the framing of news regarding presidential (capres) and vice-presidential (cawapres) candidates in the 2024 election on the websites rri.co.id and antaranews.com. The main focus of the study is how these two media outlets frame news related to the Presidential and Vice Presidential Election of the Republic of Indonesia in 2024. The objective of this research is to identify and analyze the news frames presented by both websites. The method used is a descriptive qualitative approach with framing analysis based on Robert N. Entman's model. The results show that rri.co.id provides a positive framing for the Anies-Muhaimin and Prabowo-Gibran pairs, although there are negative elements. Coverage of Ganjar-Mahfud portrays them as enthusiastic and aggressive candidates, while also highlighting the challenges they face. Meanwhile, on antaranews.com, Anies-Muhaimin is presented positively with word emphasis that influences perception, while Prabowo-Gibran is framed more critically, focusing on survey results and past defeats. Ganjar-Mahfud is also presented positively, but the coverage raises skepticism regarding their collaboration with Timnas Amin.